Вимоги до подання і зберігання науково-технічних інформаційних веб-ресурсів - Кушнірецька, Оксана; Берко, Андрій (Видавництво Львівської політехніки, 2014)
The methodology of presentation and storage of scientific and technical information resources has been described in this paper. The classification of electronic information resources has been considered. The basic requirements for the presentation and storage of scientific and technical information resources have been proposed.
Keywords: науково-технічний інформаційний ресурс; подання науково-технічних інформаційних ресурсів; зберігання науково-технічних інформаційних ресурсів; аналіз науково-технічних інформаційних ресурсів; пошук науково-технічних інформаційних ресурсів